Pengaruh uang giral dan uang kuasi terhadap inflasi di Indonesia - Fadly Fernandes; Rosyetti '; Rahmat Richard (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
In an economic of money would affect the economy of a country. Money also will affect the economy of a country because money is a tool that is used to meet the needs of human life in this day and age. Money has a strategic role in the economic of a country, especially since the main function of money is as a medium for transacting, so that at first the money is often interpreted something generally accepted as a means of payment. This research aims to empirically examine the effect of macro variables (demand deposits and Quasy-money) are inflation in Indonesia.this research uses secondary data types. The analytical method used is the method of quantitative analysis using multiple regression analysis tools SPSS version 18.0. Result of research conducted shows the results of simultaneous demand deposits and quasy-money real impact on inflation in Indonesia period 2003-2012 with F at 110,209 with sig 0,000 and the value R2at 0,960 that means 96% inflation in Indonesia is influenced by demand deposits and quasy-money, while the remaining 4% is influenced by other factors not addressed in this research.Keywords : demand deposits, quasy-money and inflation